2023
DOI: 10.1038/s41467-023-38042-2
|View full text |Cite
|
Sign up to set email alerts
|

Observation of structural switch in nascent SAM-VI riboswitch during transcription at single-nucleotide and single-molecule resolution

Abstract: Growing RNAs fold differently as they are transcribed, which modulates their finally adopted structures. Riboswitches regulate gene expression by structural change, which are sensitive to co-transcriptionally structural biology. Here we develop a strategy to track the structural change of RNAs during transcription at single-nucleotide and single-molecule resolution and use it to monitor individual transcripts of the SAM-VI riboswitch (riboSAM) as transcription proceeds, observing co-existence of five states in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
(64 reference statements)
2
4
1
Order By: Relevance
“…In the transcriptional mimicking assay, the nascent RNA displayed a weaker response to guanidine compared to the post-transcriptional counterparts. This suggests that in the guanidine-IV riboswitch system, the DNA templates and RNA polymerase play a role in RNA folding and guanidine binding, in line with the previous findings for the pre-Q1 and SAM-VI riboswitches (Widom et al, 2018; Xue et al, 2023). Moreover, the guanidine sensitivity of EC-87 indicates that guanidine regulation for the guanidine-IV riboswitch occurs before transcription of the aptamer domain is completed.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the transcriptional mimicking assay, the nascent RNA displayed a weaker response to guanidine compared to the post-transcriptional counterparts. This suggests that in the guanidine-IV riboswitch system, the DNA templates and RNA polymerase play a role in RNA folding and guanidine binding, in line with the previous findings for the pre-Q1 and SAM-VI riboswitches (Widom et al, 2018; Xue et al, 2023). Moreover, the guanidine sensitivity of EC-87 indicates that guanidine regulation for the guanidine-IV riboswitch occurs before transcription of the aptamer domain is completed.…”
Section: Discussionsupporting
confidence: 90%
“…However, Xue et al have reported similarities between T7 and E. coli RNAP in the folding of nascent RNA. Additionally, Lou and Woodson have provided valuable insights into the co-transcriptional folding of the glmS ribozyme using T7 RNAP (Xue et al, 2023; Lou & Woodson, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations